2017
DOI: 10.1515/hmbci-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in pregnancy at term: risk factors and pregnancy outcomes

Abstract: Background Vitamin D deficiency during pregnancy is a worldwide epidemic. The aim of this study was to determine the prevalence of vitamin D deficiency, its predictive factors and the association with pregnancy outcomes. Materials and methods This was a prospective observational study in a tertiary teaching hospital over 2-years' duration from August 2013 to August 2015. A total of 680 women who completed 37 weeks of pregnancy were recruited. Results Five hundred and seventy-five patients were enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
4
29
0
1
Order By: Relevance
“…Nonetheless, the studies reporting the association of these SNPs and vitamin D status were largely conducted in the non-pregnant population [19][20][21][22]. Also, previous studies examining the factors associated with VDD during pregnancy were restricted to the study of only environmental [15,23,24] or genetic factors alone [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the studies reporting the association of these SNPs and vitamin D status were largely conducted in the non-pregnant population [19][20][21][22]. Also, previous studies examining the factors associated with VDD during pregnancy were restricted to the study of only environmental [15,23,24] or genetic factors alone [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported 90% and 72% VDD (25OHD < 50 nmol/L) among pregnant women at rst trimester [15] and delivery [24], respectively. However, the prevalence reported in the present study was higher compared to our previous study conducted among pregnant women from a private hospital in Kuala…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays an important role in trophoblast invasion [46]. There are plenty of studies that prove its effects on placental implantation, angiogenesis and endothelial function, immune function, inflammatory response during pregnancy, oxidative stress, and glucose homeostasis [47][48][49][50][51][52][53]. According to Hollis and Wagner, vitamin D plays an important role in embryo and fetal skeletal development [54].…”
Section: Vitamin D -Role In Uncomplicated Pregnancymentioning
confidence: 99%
“…Nonetheless, the studies related the association of the SNPs and vitamin D status were largely conducted for the non-pregnant women [19][20][21][22]. Also, previous studies focused on the factors associated with VDD during pregnancy were restricted to the study of only environmental [15,23,24] or genetic factors only [25][26][27][28].…”
mentioning
confidence: 99%